The Design and Implementation of Regional Economic Application System Based on Supply Chain Management Model - Wu, Yun (Proceedings of the The 1st EAI International Conference on Multimedia Technology and Enhanced Learning, 2016)
The increasingly fierce competition in the retail industry, retailers must establish a new mode to reduce operating costs, reduce inventory and supply chain management idea is make capital flow, information flow, logistics, etc. various kinds of information can be timely and effective in the chain, each node open up, so as to achieve the goal of benefit maximization. Supply chain management as a kind of brand-new management idea, has become the retail companies scramble to adopt management methods, in order to solve the retail industry in the expansion of the existing various problems and contradictions, so as to enhance the core competitiveness of enterprises. The progress of IT Technology (especially Internet technology) provides the possibility for the realization of supply chain management. In the process of supply chain management, the integration of information technology has played a great role in the support of the high efficiency and efficiency of the supply chain. Effective supply chain management information system, which is suitable for its own development, has become the most important task in the management of Chinese retail enterprises. This paper mainly analyzes the structure and function module of the retail supply chain management information system. And through the case analysis of WAL-MART supply chain management information system, the structure of the system to carry out a preliminary proof, in order to form the guiding role of China's retail industry. Finally, it describes the application of electronic data exchange technology, radio frequency identification technology, GIS and GPS and other information technology in the supply chain management.